Penggunaan Media Video Pembelajaran dalam Meningkatkan Motivasi Belajar Anak Usia Dini di Masa Pandemi - Rika Gustiani; Ine Nirmala.; Feronica Eka Putri; Siti Istiqomah . (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2021)
This research article aims to describe the process and result of learning using instructional video media made by teachers in increasing children’s leaning motivation during the pandemic. This research was conducted at Baitul Falihin KB, Karawang in June 2021. The subjects of this study were children aged 5-6 years, totaling 10 children’s. The research method used in classroom action research. Data collection techniques are through observation, interviews and documentation. Data analysis techniques used in this study are qualitative and quantitative data analysis. Quantitative data analysis is used to determine the percentage increase in children’s learning motivation after the action. Qualitative analysis is used to describe the research result. The results showed an increase in children’s learning motivation after learning using learning video media. Based on the results of research conducted in cycle I and cycle II, the results of cycle I showed an increase of 50.4%, and in the second cycle showed an increase of 79.2%. These results can be used as a reference for teachers to use learning video media as a medium to increase children’s motivation